Non cooperative stackelberg network formation. (2014)
Non-cooperative network formation games in industrial organizations analyzehow firms create links. We assume that links portray cost-reducing informationand that access to this information is not reciprocal. We study the consequences interms of profits if one firm can move first in establishing a link. A classic modelof exogenous Stackelberg leadership is developed and first-mover advantage isobserved.